2012
DOI: 10.5937/jaes10-2130
|View full text |Cite
|
Sign up to set email alerts
|

Systemic assessment and analysis of factors affect the reliability of a wind turbine

Abstract: Nowadays, the availability of wind turbines usually approaches the 98%. The objective is to increase the turbines availability, by improving the wind turbine reliability especially for offshore plants. The wind turbines reliability is a pivotal factor in the successfully function of a wind power plant. High reliability can be achieved by understanding and minimizing the failures of the system. Maintenance planning could make maintenance more effi cient and could lead to a reduction of failure events. In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…They identified that all four wind farms have reasonable wind energy potential, but that the Gulf of Mexico has a high probability of wind speeds >50 m s −1 under tropical cyclone conditions, representing a high tropicalcyclone-related risk for wind farm constructions. In addition, many scholars have conducted hazard assessment of wind turbines using decision making methods such as failure modes and effect analysis (FMEA), support vector machine (SVM), and fault tree analysis (FTA) with certain results (Pantelis et al, 2012;Sinha and Steel, 2015;Zhang et al, 2016;Kang et al, 2017Kang et al, , 2020. However, among these methods, the FMEA method focuses on individual turbine equipment and requires that all failure modes of the turbine must be known before the evaluation, otherwise the evaluation results will be wrong, but the damage caused by tropical cyclones to the turbine structure is not deterministic.…”
Section: Introductionmentioning
confidence: 99%
“…They identified that all four wind farms have reasonable wind energy potential, but that the Gulf of Mexico has a high probability of wind speeds >50 m s −1 under tropical cyclone conditions, representing a high tropicalcyclone-related risk for wind farm constructions. In addition, many scholars have conducted hazard assessment of wind turbines using decision making methods such as failure modes and effect analysis (FMEA), support vector machine (SVM), and fault tree analysis (FTA) with certain results (Pantelis et al, 2012;Sinha and Steel, 2015;Zhang et al, 2016;Kang et al, 2017Kang et al, , 2020. However, among these methods, the FMEA method focuses on individual turbine equipment and requires that all failure modes of the turbine must be known before the evaluation, otherwise the evaluation results will be wrong, but the damage caused by tropical cyclones to the turbine structure is not deterministic.…”
Section: Introductionmentioning
confidence: 99%